Meaning and Scope of Stylistics - Manreet Dhaliwal, (The Creative Launcher, 2017)
The present paper presents the meaning and scope of stylistics. Stylistics is an analytical mode of analysis that combines linguistics and literary criticism and includes different levels of phonology, prosody, morphology, syntax, etc. Stylistics analyzes literary discourse through linguistic perspective. The present paper examines how ‘stylistics’ becomes significant as it tries to link the two approaches. Some theoreticians consider it a branch of linguistics and a domain of mediation between linguistics and literary criticism and some consider it an independent branch that investigates the same phenomenon from its own perspective. The paper also discusses conflicting approaches to stylistics.